2001
DOI: 10.1016/s0003-4878(00)00028-4
|View full text |Cite
|
Sign up to set email alerts
|

Allergen and dust exposure as determinants of work-related symptoms and sensitization in a cohort of flour-exposed workers; a case–control analysis

Abstract: Objectives: To estimate the incidence of specific IgE sensitization and allergic respiratory symptoms among UK bakery and flour mill workers; and to examine the roles of flour aeroallergen and total dust exposures in determining these outcomes.Methods: A cohort of 300 new employees, without previous occupational exposure to flour, were followed prospectively for a median (range) of 40 (1-91) months. Cases-defined as those developing work-related symptoms or a positive skin prick test to flour or a-amylase duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(65 citation statements)
references
References 11 publications
2
61
2
Order By: Relevance
“…Workers in the industrialized bakeries had a four times higher risk of becoming sensitized at the same exposure level as workers in the flour mills and a twice as high risk as workers in the bakery-ingredient industry. Therefore, the sector of industry may serve as a proxy for the kind of dust mixture to which workers are exposed, as well as for the local environment (eg, temperature, degree of use of ventilation devices) or may represent individual characteristics [other than age, gender, or cigarette smoking, such as atopy (17)], which contribute to the differences between industries. The difference in the prevalence in atopy between the industries seems to be a key explanatory variable.…”
Section: Exposure-response Relationshipmentioning
confidence: 99%
“…Workers in the industrialized bakeries had a four times higher risk of becoming sensitized at the same exposure level as workers in the flour mills and a twice as high risk as workers in the bakery-ingredient industry. Therefore, the sector of industry may serve as a proxy for the kind of dust mixture to which workers are exposed, as well as for the local environment (eg, temperature, degree of use of ventilation devices) or may represent individual characteristics [other than age, gender, or cigarette smoking, such as atopy (17)], which contribute to the differences between industries. The difference in the prevalence in atopy between the industries seems to be a key explanatory variable.…”
Section: Exposure-response Relationshipmentioning
confidence: 99%
“…This type of study has recently been successfully applied in cohorts of young apprentices [4][5][6][7][8][9][10]. Some case-referent studies have been carried out in the field of OA [11,12]. These studies are valuable in identifying and quantifying risk factors.…”
mentioning
confidence: 99%
“…It was found that several sources are responsible for emission of these bioaerosols in air. These sources include natural sites such as soil, water, plants and animals and human as well as anthropogenic like agricultural practices, healthcare units and industrial operations (Cullinan et al, 2001). Bioaerosols contribute to about 5-34% of indoor air pollution (http://www.pollutionissues.com/Ho-Li/Indoor).…”
Section: Introductionmentioning
confidence: 99%